Clinical evolution of Parkinson's disease and prognostic factors affecting motor progression: 9‐year follow‐up study. (2nd June 2014) - Reinoso, G.; Allen, J. C.; Au, W.‐L.; Seah, S.‐H.; Tay, K.‐Y.; Tan, L. C. S.
<x xml:space="preserve">Abstract</x> Background and purpose There have been few long‐term studies that have characterized and charted the clinical progression of Parkinson's disease (PD). This study was therefore undertaken to understand the natural clinical evolution of treated PD patients and to identify the variables that predict greater progression in these patients. Methods A longitudinal linear mixed model analysis of motor score progression was performed on 576 PD patients derived from the National Neuroscience Institute Movement Disorders Database. Clinical and demographic variables were taken at baseline and formed the subgroups for comparison (gender, age at diagnosis, subtype, Mini‐Mental State Examination score and baseline motor score). Motor score progression was calculated at each patient follow‐up time point as the difference between Unified Parkinson's Disease Rating Scale (UPDRS) motor score at baseline and follow‐up scores. Results The overall annual motor score progression as measured by the change of UPDRS motor scores from baseline ranged from 0.62% to 3.67%. There are three distinct phases: improvement, stability, and steady progression. Patients returned to baseline score 2–2.5 years after diagnosis, with stability lasting to 7 years, followed by a period of steady progression. When analyzed longitudinally, male gender (P < 0.03), older age at diagnosis (P < 0.05), akinetic‐rigid subtype (P < 0.04), cognitive impairment (P < 0.005) and lower baseline motor score (P < 0.04) were associated with greater progression of motor scores. Conclusions Our results show that, when measured clinically, motor progression was non‐linear and that it occurred in distinct phases, all of which were affected by baseline demographic and clinical variables such as gender, age at diagnosis, disease subtype, cognitive status and baseline motor score.